Peran Ekonomi Kreatif Melalui UMKM Dalam Mewujudkan Pariwisata Berkelanjutan - Haeril; Dinesh Basti Farani; Jemadi; Sulaiman Efendi Siregar; Eko Budi Lestari (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
The purpose of this study is to determine and analyze the role of the creative economy through MSMEs in realizing sustainable tourism. This research approach collects data through literature studies, which involve reading literature from various sources including books, journals and reports using qualitative and deductive approaches. The findings in this study are that the creative economy through MSMEs has a very important role in realizing sustainable tourism. There are several ways for the creative economy through MSMEs to realize sustainable tourism including the advancement of local culture, development of local products and services, innovation and collaboration, increasing local community participation, homestays and local investment, and environmental preservation.